Paradise Disenchanted: Globalization, Postmodernism, and Their Discontents in Selected Late 20th Century Novels - Xing, Xianghui. (Tufts University. Tisch Library., 2019)
Abstract: My dissertation, Paradise Disenchanted: Globalization, Postmodernism, and Their Discontents in Selected Late 20th Century Novels, examines three late 20th century novels in English: Don DeLillo's Mao II (1991), Chang-rae Lee's Native Speaker (1995), and Michelle Cliff's No Telephone to Heaven (1987). Drawing on theories on globalization and postmodernism, I argue that despite these authors' diverse socioeconomic conditions and varying ideological alliances with postmodernist culture, their novels all display, at various levels, discontent with globalization and its cultural politics as manifested in postmodernism. I also bring attention to the ideological nuances and differences in these novels. Particularly, Don DeLillo's Mao II (Chapter One) and Michelle Cliff's No Telephone to Heaven (Chapter Three) present a stark contrast in their respective critique of globalization's economic ramifications and postmodernism's political impact from very different angles and concerns. Ultimately, the dissertation will reveal that although proponents of globalization and postmodernism make a series of promises, such as post-industrial and post-colonial economic development, accessible surplus consumer goods, and celebration of multiculturalism, the rosy picture of global paradise remains largely an unfulfilled and undelivered myth. While all three texts under discussion voice their disenchantment and dissent towards globalization and postmodernism, saliently, Cliff's No Telephone to Heaven stands out. The novel is daring in providing not only an artistic imagination of grassroots resistance, but also a sane caution against resistance pitfalls out of a dialectical and historical perspective.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of English.; Advisor: Modhumita Roy.; Committee: Elizabeth Ammons, Nathan Wolff, and Kristina Wright.; Keywords: English literature, American literature, and Caribbean literature.